Testing the Processing-Induced Roughness of Sanded Wood Surfaces Separated from Wood Anatomical Structure - Gurau, Lidia (MDPI AG, 2022)
The metrology of processed wood surfaces is complex due to the presence of wood anatomical cavities, which are a factor of bias in several metrological steps, from the measuring to the evaluation of the surface quality. Wood requires special recommendations, and one regards the use of a robust Gaussian regression filter for filtering the roughness. The filter was previously tested with success on wood surfaces and was used in this paper. Furthermore, a reliable quantification of the processing roughness requires that independent wood anatomical data be removed from the evaluation. The paper presents a method of separating the roughness induced by processing from the wood anatomical structure. It was tested on different wood species, sanded with various grit sizes, and on a plastic material included for comparisons. The results showed similar values of the processing roughness for materials sanded with the same grit size, in spite of their different structures. The method could further be used for optimization of processing parameters at sanding.
Keywords: processing roughness; wood anatomical structure; separation; sanding